On Cooperation in Musgravian Models of Externalities within a Federation - Henry Tulkens (Center for Economic Studies and ifo Institute (CESifo), 2002)
Musgravian externalities, formulated and illustrated by Musgrave in a 1966 paper on social goods are seen in this paper as one form of the interactions that occur between the components of a federation. The original formal apparatus is first exposed briefly. In that context, it is then considered whether and how alternative forms of federal structures are likely to achieve efficiency. Following suggestions from the literature, three such forms are dealt with: planned, cooperative and majority rule federalisms. Next, the relevance of non cooperative equilibria is examined, in the light of an interpretation of them as fall back positions when disagreement occurs among members of a federation. Finally, the question is evoked of what economics and public finance may have to say on the limits to institutional decentralization, i.e. on the choice between federal, confederal and secessional structures. The paper concludes with a reminder of Musgrave's view on this issue.
Keywords: 330